Improving Islamic Religious Education Learning through the Method of Giving Learning Assignments and Recitations at SD Negeri 100580 Sayur Matinggi - Nurhalilah (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2025)
Islamic Religious Education (PAI) learning has an important role in shaping the character of students so that they have good morals in accordance with Islamic values. However, in practice, the effectiveness of PAI learning often faces various obstacles, such as low student involvement in the learning process and lack of learning motivation. This study aims to improve the quality of PAI learning through the application of the method of giving learning assignments and recitations at SDN 100580 Sayur Matinggi. The research method used is classroom action research (CAR) which consists of four stages, namely planning, implementation, observation, and reflection. The results of the study showed that the application of the method of giving learning assignments and recitations was able to improve students' understanding of PAI material, strengthen their memory, and increase their activeness and participation in learning. In addition, this method also encourages independent learning, because students are required to complete tasks independently and repeat the material that has been studied. Thus, the method of giving learning assignments and recitations can be an effective solution to improve the quality of PAI learning. Therefore, this method is recommended for educators as an alternative strategy in optimizing student learning outcomes in PAI subjects.